Integrability Meets the Charged Relativistic Particle - Correa, F (Elsevier B.V., 2024)
We notice an analogy between the motion of a relativistic particle in external homogeneous and time-dependent electromagnetic fields and the Dikii-Eilenberger equation for the Bogoliubov-de Gennes equation. By means of the integrable defocusing nonlinear Schrödinger hierarchy and their solitons appearing in the Gross-Neveu and Nambu-Jona-Lasinio models, we construct an infinite family of solutions of the Lorentz equation with non-vanishing curvature and torsion of the worldline trajectory. © 2024 The Author(s)